2020
DOI: 10.1002/cnr2.1280
|View full text |Cite
|
Sign up to set email alerts
|

Gynaecologic cancer care during COVID‐19 pandemic in India: a social media survey

Abstract: Background: Health care services across the globe are undergoing a major transformation to combat the coronavirus disease 2019 (COVID-19) pandemic. Regardless of the strength of health care infrastructure across different economies, all countries are diverting their resources toward care for COVID-19 patients. Aim: The aim of this survey was to evaluate the pattern of care of gynaecologic cancers in a developing country during the COVID-19 pandemic. Methods: An anonymous survey consisting of 20 questions inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Overall, 65% [c.i. 53%-75%, I 2 98%, number of studies: 14 ( 27 – 29 , 36 38 , 42 44 )] of studies reported some modification of the treatment regimens or surgical interventions. The moderator variable which alone explained the most heterogeneity was the geographical area in which the study was conducted (n=9, R 2 31%, I 2 96.9%, p-value for the test of moderators in meta-regression=0.02).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 65% [c.i. 53%-75%, I 2 98%, number of studies: 14 ( 27 – 29 , 36 38 , 42 44 )] of studies reported some modification of the treatment regimens or surgical interventions. The moderator variable which alone explained the most heterogeneity was the geographical area in which the study was conducted (n=9, R 2 31%, I 2 96.9%, p-value for the test of moderators in meta-regression=0.02).…”
Section: Resultsmentioning
confidence: 99%
“…A survey of providers across India (61 total respondents, 63.9% gynecologic oncologists, 18% radiation oncologists) noted that 95% of respondents felt that COVID-19 had modified their patterns of care for patients with gynecologic cancer. Additionally, 40.9% of respondents said they provided radiation to cases based on an urgency scale, and 9% reported having implemented hypofractionation in response to the pandemic 18…”
Section: Real World Accountsmentioning
confidence: 99%
“…Additionally, 40.9% of respondents said they provided radiation to cases based on an urgency scale, and 9% reported having implemented hypofractionation in response to the pandemic. 18…”
Section: Real World Accounts Asia Pacificmentioning
confidence: 99%
“…The available published data on, international recommendations for, and global experience with infections in cancer patients may help overcome the challenges described above 2,12–14 . Nevertheless, our understanding of the COVID‐19 pandemic is evolving, and the oncologic surgery workflow must be revisited, updated, and optimized as a result to account for the range of institutional, local, and national conditions during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The available published data on, international recommendations for, and global experience with infections in cancer patients may help overcome the challenges described above. 2 , 12 , 13 , 14 Nevertheless, our understanding of the COVID‐19 pandemic is evolving, and the oncologic surgery workflow must be revisited, updated, and optimized as a result to account for the range of institutional, local, and national conditions during the pandemic. Therefore in this systematic review, meta‐analysis, and meta‐regression, we analyzed the measurable reported outcomes and identified potential predictors of poor outcome in cancer patients who had oncologic surgery during the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%